Model Dakwah Kolaboratif Pemuda Persatuan Islam di Kampung Bantarpanjang Pulau Nusakambangan - Syamsudin, Kinkin; Rustandi, Ridwan (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2023)
This research analyses the collaborative da'wah model by the Islamic Unity Youth (Pemuda Persis) in Bantarpanjang Village, Nusakambangan Island, Central Java. This article focuses on three problems: the objective conditions of the Bantarpanjang community, the da'wah problems faced, and the model of da'wah carried out by the Islamic Unity Youth preachers. Data was obtained through document analysis, interviews, discussions and direct observation in the field. The research results show that, first, Bantarpanjang Village is very remote in location; there is no infrastructure to support social activities, and the road to the location is quite an obstacle; second, the level of Islamic understanding of Bantarpanjang residents is still low and most of the residents are still illiterate in reading and writing the Koran; third, Islamic Unity Youth (Pemuda Persis) preachers carry out da'wah in the form of regular weekly guidance and collaborate with other parties in carrying out social services.